2001
DOI: 10.1096/fj.00-0702fje
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone restores glucocorticoid‐induced T cell suppression

Abstract: Growth hormone (GH) is a potent anabolic hormone, and its clinical use has been extended to the improvement of metabolic imbalance in many disease,s including autoimmune disorders treated with glucocorticoids (GCs). GH has, however, a potential action on the immune system, and this might be a demerit in GH therapy for those diseases. We report here the anti‐GC effects of GH on T lymphocytes. Human peripheral T lymphocytes (HPTLs) expressed GH receptor mRNA. GH stimulated tyrosine phosphorylation of cellular pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…Interestingly, we previously reported that hGH prevented glucocorticoid-induced apoptosis in human peripheral T lymphocytes. This antiapoptotic effect, however, was detected in CD4+ but not in CD8+ T lymphocytes [24]. hGH enhanced the expression of Bcl-2 at both the protein and mRNA level in human peripheral CD4+ T lymphocytes.…”
Section: Discussionmentioning
confidence: 77%
“…Interestingly, we previously reported that hGH prevented glucocorticoid-induced apoptosis in human peripheral T lymphocytes. This antiapoptotic effect, however, was detected in CD4+ but not in CD8+ T lymphocytes [24]. hGH enhanced the expression of Bcl-2 at both the protein and mRNA level in human peripheral CD4+ T lymphocytes.…”
Section: Discussionmentioning
confidence: 77%
“…LEC treatment with GH inhibited LEC apoptosis, in accordance with previous results in other cell types including mammary carcinoma cells 49 and in T cells. 50 Previous studies have indicated that several lymphangiogenic factors might mediate their effects on LECs indirectly via paracrine or autocrine effects leading to activation of VEGFR-2 or VEGFR-3. In particular, the lymphangiogenic activity of basic fibroblast growth factor was inhibited by blockade of VEGFR-3 signaling.…”
Section: Discussionmentioning
confidence: 99%
“…A common clinical result of this change in the hormonecytokine ratio is that the biological effect of the hormone is impaired by a proinflammatory cytokine, thereby leading to endocrine resistance. For example, dexamethasone inhibits proliferation of human T cells, and this effect is partially reversed by increasing the ratio of hormones by addition of exogenous GH and IGF-I (Dobashi et al, 2001). Unfortunately, we do not yet know the critical events that occur inside proliferating T cells when they are exposed to both IGF-I and dexamethasone.…”
Section: And Beyondmentioning
confidence: 99%